2015
DOI: 10.1007/s00464-015-4189-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional versus two-dimensional vision in laparoscopy: a systematic review

Abstract: Overall, 3D laparoscopy appears to improve speed and reduce the number of performance errors when compared to 2D laparoscopy. Most studies to date assessed 3D laparoscopy in simulated settings, and the impact of 3D laparoscopy on clinical outcomes has yet to be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(178 citation statements)
references
References 42 publications
8
169
0
1
Order By: Relevance
“…Most of these studies have been conducted using an experimental surgical model [19,25]. A recent review reported a lower rate (63% of the trials) of errors with the use of 3D system [9,26]. Storz P. et al [25] concluded that the use of 3D might be of minor importance in simple tasks, but it can increased task efficiency when performing difficult surgical tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been conducted using an experimental surgical model [19,25]. A recent review reported a lower rate (63% of the trials) of errors with the use of 3D system [9,26]. Storz P. et al [25] concluded that the use of 3D might be of minor importance in simple tasks, but it can increased task efficiency when performing difficult surgical tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Although 3D technology was introduced in the early 1990s its equipment is still not standard in hospital because of initial observation of side effects when using 3D vision systems, poor image resolution and more expensive cost [8]. In literature there are still few clinical studies on use of 3D with different results [9]. In this study we report our experience with use of 3D vision system for laparoscopic adrenalectomy.…”
Section: Introductionmentioning
confidence: 97%
“…Sorensen et al [22] showed that 3D laparoscopic vision improves speed and reduces the number of performance mistakes when compared to 2D laparoscopic vision. In this manner, the efficacy and visual perception can be increased in fresh-frozen cadaveric model for laparoscopic training purpose by using 3D laparoscopic system.…”
Section: Anatomic Laparoscopic Prostatectomy Modelmentioning
confidence: 99%
“…A review of the literature has shown that 3D laparoscopy seems to improve the speed and reduce the performance errors compared with 2D laparoscopy. 11 Aykan and associates have shown that 3D laparoscopic radical prostatectomy is associated with shorter operation time, less blood loss, and higher early continence rates than conventional 2D laparoscopy. 12 However, an early randomized clinical trial on laparoscopic cholecystectomy did not show any evidence that 3D was superior to 2D.…”
Section: Evaluation Of Three-dimensional Versus Conventional Laparoscmentioning
confidence: 99%
“…13 It is still unclear whether 3D laparoscopic equipment can improve the proficiency in performing complex laparoscopic surgeries as most of these studies have been conducted in simulated settings using tasks whose face validity might be questioned compared with human organ transplant. 11 Therefore, the aim of this study was to evaluate a 3D, high-definition (3DHD) system versus a 2D laparoscopic system in performing a complex procedure of kidney transplant with a human cadaveric training model.…”
Section: Evaluation Of Three-dimensional Versus Conventional Laparoscmentioning
confidence: 99%